SAT0617-HPR QUALITATIVE STUDY EXPLORING THE BARRIERS AND FACILITATORS TO HOME-BASED EXERCISE PROGRAMS ADHERENCE WITH KNEE OSTEOARTHRITIS: THE PERSPECTIVES PHYSIOTHERAPISTS AND PATIENTS. (13th June 2020) - Akgül, H.; Sermenlİ Aydin, N. and Sari, Z. and Bİrtane, M. and Tonga, E.
Abstract : Background: Home exercise programs are widely used in the treatment of knee osteoarthritis (OA). However, adherence to these exercises decreases in the long term due to different factors. In recent years, new approaches are being developed to increase exercise adherence (EA) for patients with OA. Although it is known that EA is low in Turkish patients, there is no study that examines the barriers of adherence to home exercise programs in patients with OA by qualitative research methods. Objectives: Aim of our study was to investigate the barriers and facilitators for adherence of home-based exercises for knee osteoarthritis management from the perspective of physiotherapists and patients. Methods: A Qualitative study by using focus groups discussions and semi-structured interviews were designed to investigate the barriers and facilitators to home-based exercise program adherence for OA. Two researchers facilitated focus group interview. Participants of focus group members were eight physiotherapists (PT) working with OA with different experience levels. Third researcher conduct the interviews which lasted 30-60 minutes with patients (patients with knee OA, n=5 ages>50). Data were audio recorded, transcribed verbatim and thematically analyzed with NVIVO 12 software. Three researchers conducted the thematic analysis to ensure the validity. Results: In total, 25 main themes from the focus group discussions and interviews were determined. Major barrier themes from focus group were (a) beliefs to exercise benefits (b) patient education and (c)fear avoidance beliefs on exercise; from the interviews were (a)negligence of self-management (b)fatigue and (c)patient education. Patients and therapists all agreed for patient education is one of the most important factors for home EA. Patients wanted to get education on arthritis management. A patient said: "Actually, the clinicians should give information more deeply. I don't know which is correct for me after therapy, resting or moving?" Major facilitator themes from the focus group were (a)motivation from PT (b)client-centred exercise (c)digital technology; from interviews were (a) motivational approaches of therapists (wats-up messages) (b) having pain and (c)patient education for disease management. Therapists agreed on that personalized exercise is the most important facilitator. A therapist commented, "If the personalized exercise given the patient with correct intensity and repetitions, I don't think that patients would not do their home exercises." Conclusion: This is the first qualitative study about exercise adherence in knee osteoarthritis in Turkey. It has been determined that the lack of education and motivation are the most important barriers. More studies are needed to examine the factors affecting EA for patients with OA. In future studies, implementations to increase home EA on Turkish patients with OA should be investigated by qualitative research methods. References: [1]MacKay C. Qualitative study exploring the factors influencing physical therapy management of early knee osteoarthritis in Canada. BMJ 2018 open. [2]Carmona-Terés, Understanding knee osteoarthritis from the patients' perspective: a qualitative study." BMC musculoskeletal disorders 18.1 (2017): 225. [3]Marlene F.Exercise for osteoarthritis of the knee: a Cochrane systematic review. British journal of sports medicine 2015 49(24). Disclosure of Interests: None declared